283 Salvage Versus Primary Robot-Assisted Radical Prostatectomy: A Propensity-Matched Comparative Effectiveness Study from A High-Volume Tertiary Centre. (12th October 2021) - Nathan, A; Fricker, M; De Groote, R; Arora, A; Phuah, Y; Flora, K; Patel, S; Kasivisvanathan, V; Sridhar, A; Shaw, G; Kelly, J; Briggs, T; et al.
Abstract: Aim: Salvage Robot-Assisted Radical Prostatectomy (sRARP) is a potential treatment option for locally recurrent Prostate Cancer after non-surgical primary treatment. There are minimal data comparing outcomes between propensity-matched salvage and primary Robot-Assisted Radical Prostatectomy (RARP). We compare perioperative, oncological, and functional outcomes of sRARP with primary RARP and between sRARP post-whole and focal gland therapy. Method: 1:1 propensity-matched comparison of 146 sRARP with primary RARP from a cohort of 3, 852 consecutive patients from a high-volume tertiary centre. Results: There were no significant differences in patient characteristics between the salvage and primary RARP groups. Grade III-V Clavien-Dindo complication rates were 1.3% and 0% in the salvage and primary groups, respectively (p = 0.310). Median (IQR) follow-up was 16 (10, 30) and 21 (13, 33) months in the salvage and primary groups, respectively. BCR rates were 30.8% and 13.7% in the salvage and primary groups, respectively (p < 0.001). Pad-free continence rates were 79.1% and 85.4% at two years in the salvage and primary groups, respectively (p = 0.160). ED rates were 95.2% and 77.4% in the salvage and primary groups, respectively (p < 0.001). Comparing the whole gland and focal gland groups, BCR rates were 33.3% and 29.1%, respectively (p = 0.687), pad-free continence rates were 66% and 89.3%, respectively (p = 0.001), and ED rates were 98.3% and 93%, respectively (p = 0.145). Conclusions: SRARP has similar perioperative but inferior oncological outcomes to primary RARP. Continence rates are similar to primary RARP, but potency is worse. Perioperative and oncological outcomes of sRARP after focal gland therapy are similar but continence outcomes are superior compared to sRARP after whole gland therapy.